KONTRIBUSI KREDIBILITAS TERHADAP KINERJA PENGAWAS PENDIDIKAN AGAMA ISLAM - Muhammad Fazis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2008)
This article is a part of study on the contribution of credibility and achievement motivation toward performance of supervisor for Islamic teaching teachers (PAI) at state elementary schools in West Sumatera. Based on preliminary observation, it was found that the performance of the supervisor was low due to some assumed factors, such as low credibility. This study was, therefore, to elaborate such contribution. The formulated hypothesis proposed was credibility contributed toward performance of supervisor for Islamic teaching teachers (PAI) at state elementary schools in West Sumatera. This was a correlational study in which all supervisors for Islamic teaching teachers (PAI) at state elementary schools in West Sumatera were taken as the population. The sample was determenined by following Cochran’s formula. Likert’s scale questionnaire was used to collect the data after validity and reliability had been achieved. The data then were analysed by employing simple correlational and regressional techniques. The findings showed that the hypothesis was empirically accepted. Credibility contributed 15.2% toward performance of supervisor for Islamic teaching teachers (PAI) at state elementary schools. Credibility was categorized fair (65.22% out of maximum score) and performance of supervisor for Islamic teaching teachers (PAI) at state elementary schools was categorized fair (79.38% out of maximum score).Kata Kunci: kredibilitas, kinerja, pengawas pendidikan agama Islam, sekolah dasar negeri